PENGARUH PENERAPAN CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN DENGAN UKURAN PERUSAHAAN DAN LEVERAGE SEBAGAI VARIABEL KONTROL - Christine Arianto Salim; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study aimed to prove that corporate governance had positive affect on financial performance of companies that are listed in CGPI scoring. Corporate governance was measured by using CGPI that implemented by IICG. Financial performance was measured by using Return On Equity. This study also used control variables of firm size and leverage and variable dummy in the form of financial crisis which happened in 2008-2009. This study examined companies that listed in CGPI scoring period 2001-2015 with sample of 248 observations. The results showed that corporate governance had positive significant affect on financial performance. The results also showed that firm size, leverage, and financial crisis had no affect on financial performance.